From Diagnosis to Treatment: Advances in Clinical Research on Severe Pneumonia - Sheng Wang; Xiaoli Wu; Xiaoshuai Wu (Journal of Artificial Intelligence and Information, 2026)
Severe pneumonia is a life-threatening infectious disease associated with high mortality and is frequently complicated by acute respiratory distress syndrome, septic shock, and multiple organ dysfunction. The current diagnostic and therapeutic paradigm is shifting from empirical broad-spectrum treatment toward individualized management based on precise pathogen identification and assessment of the host response. The pathogenesis of severe pneumonia involves a broad range of bacterial, viral, and fungal pathogens, together with complex pathophysiological processes including dysregulated inflammation, immune dysfunction, and coagulation abnormalities. Conventional pathogen-detection methods are limited by low sensitivity and prolonged turnaround times. Emerging molecular diagnostic technologies have substantially increased pathogen detection rates and facilitated early, targeted anti-infective therapy, while biomarkers have improved inflammatory monitoring and prognostic assessment. This review summarizes contemporary evidence on the etiological features of severe pneumonia, advances in diagnostic technologies, optimization of treatment strategies, and integrated models of care, with the aim of providing a theoretical basis for improved clinical management and outcomes.